In vitro and in vivo evaluation of anti-HER2 antibody conjugates labelled with 225Ac - Ondrák Fialová, Kateřina; Ondrák, Lukáš; Vlk, Martin; Kozempel, Ján; Nováková, Kateřina; Nový, Zbyněk; Hajduová, Katarína; Hajdúch, Marián; Petřík, Miloš; Pruszynski, Marek; Bruchertseifer, Frank; Morgenstern, Alfred (EJNMMI radiopharmacy and chemistry, 2025)
BACKGROUND: Overexpression of human epidermal growth factor receptor type 2 (HER2) occurs in multiple carcinomas. For example, up to 20% of breast cancer cases are classified as HER2 positive (HER2+). Treatment of this condition typically involves immunotherapy using monoclonal antibodies, such as trastuzumab or pertuzumab. The precise targeting of monoclonal antibodies to HER2+ tumour lesions can be used as well in radioimmunotherapy to deliver medical radionuclides exactly to the afflicted area and therefore minimize radiation exposure of healthy tissues. In this study, DOTA conjugates of monoclonal antibodies trastuzumab and pertuzumab were prepared and tested in vitro. One of these, 225Ac-DOTA-pertuzumab, was also the subject of an ex vivo biodistribution study with normal as well as HER2+ and HER2- tumour-xenografted mice. This radioconjugate has not been previously described. RESULTS: Three DOTA-conjugates of HER2 targeting monoclonal antibodies, one of trastuzumab and two of pertuzumab, were prepared and radiolabelled with 225Ac in different molar ratios. This procedure led to an optimisation of the preparation and radiolabelling process. The radioconjugates were shown to be highly stable in vitro in both fetal bovine serum and phosphate buffered saline under room temperature and decreased temperature for 10 days. In vitro cell studies with HER2-overexpressing cell-line (SKOV-3) and low HER2-expressing cell line (MDA-MB-231) proved that radioconjugates of both antibodies have high binding specificity and affinity towards HER2 receptors. These findings were confirmed for a novel radioconjugate 225Ac-DOTA-pertuzumab in an ex vivo biodistribution study, where uptake in HER2+ tumour was 50 ± 14% ID/g and HER2- tumour showed uptake comparable with healthy tissues (max. 5.0 ± 1.7% ID/g). The high uptake observed in the spleen can be attributed to the elimination of the antibody, as well as the use of an immunedeficient mouse strain (SCID). CONCLUSIONS: During this study, the optimization of preparation and radiolabelling of HER2 targeting antibodies with 225Ac was accomplished. Furthermore, the radioconjugate 225Ac-DOTA-pertuzumab was prepared and evaluated for the first time. The radioconjugates of both tested antibodies demonstrated excellent qualities in terms of stability and HER2 receptor affinity. Initial ex vivo studies indicated that especially the radioconjugate 225Ac-DOTA-pertuzumab is a very promising candidate for further more detailed in vivo studies.
Keywords: Pertuzumab; Actinium-225; SKOV-3; HER2; MDA-MB-231; Trastuzumab; Targeted alpha therapy